Measurements and radiation distribution along the structure of a mobile phone - Zain A.F.M.; Rhazali Z.A.; Mohamad S. (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper presents radiation emission measurements from a mobile phone. Measurements are conducted during the mobile when it is in standby, receive, and transmit mode based on the CISPR and EMC standards. The results obtained are in the form of electrical field strength observed in three different domains, i.e., frequency, time, and radiation distribution along the mobile phone structure. The mobile phones used are grouped according to the placement of the antenna either internal or external. It is found that the radiated emission is 65% higher during transmission rather than on standby. Radiation from the phone with the external antenna can be further reduced using an EWI radiation filter. 2003 IEEE.